2004
DOI: 10.2174/1381612043452758
|View full text |Cite
|
Sign up to set email alerts
|

Heparins and Heparinoids: Occurrence, Structure and Mechanism of Antithrombotic and Hemorrhagic Activities

Abstract: The correlation between structure, anticlotting, antithrombotic and hemorrhagic activities of heparin, heparan sulfate, low molecular weight heparins and heparin-like compounds from various sources that are in used in clinical practice or under development is briefly reviewed. Heparin-like molecules composed exclusively of iduronic acid 2-O-sulfate residues have weak anticlotting activities, whereas molecules that contain both iduronic acid 2-O sulfate, iduronic acid and small amounts of glucuronic acid, such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
76
0
4

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(80 citation statements)
references
References 41 publications
0
76
0
4
Order By: Relevance
“…Studies on the ability of heparin to facilitate thrombin inactivation by antithrombin have also suggested that heparin possesses catalytic properties (11,(53)(54)(55)(56). In this case, heparin appears to act as a scaffold that brings together the two proteins to facilitate the formation of the complex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on the ability of heparin to facilitate thrombin inactivation by antithrombin have also suggested that heparin possesses catalytic properties (11,(53)(54)(55)(56). In this case, heparin appears to act as a scaffold that brings together the two proteins to facilitate the formation of the complex.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggest that mast cell heparin promotes mitosis and migration of endothelial cells (10). Moreover, the anticoagulant properties of heparin prevent the formation of thrombi in the newly formed vessels (11). Other studies show that heparin has the ability to inhibit tumor growth and metastasis (12)(13)(14)(15), and there is some evidence that it may do so through an indirect mechanism, by interfering with the interaction between fibroblasts and the adjacent tumor cells (16).…”
mentioning
confidence: 99%
“…The sulfated galactofucan is 2-fold more potent than heparin. In addition, this effect was only observed for heparan sulfate synthesis similar to the effect of heparin (4,36,39,56). Because the synthesis of the heparan sulfate by endothelial cells in culture exposed to the fucan requires ϳ4 -6 h for the full effect (results not shown), it explains the delay to detect the antithrombotic effect of the algal polysaccharide on the experimental model of thrombosis.…”
Section: Dissociation Of the Anticoagulant And Antithrombotic Activitmentioning
confidence: 96%
“…Sulfated polysaccharides (SP) are compounds which posses several biological activities like as anticoagulant, antiviral, antioxidant, antitumor, antiprotozoal, anti-inflammatory, anticomplementary, antipeptic (Nader et al, 2004, Pomin, 2010. They occur in a great variety of animals, including the sulfated glycosaminoglycans found in vertebrates and invertebrates animals (Nader et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…They occur in a great variety of animals, including the sulfated glycosaminoglycans found in vertebrates and invertebrates animals (Nader et al, 2004). Furthermore, marine invertebrate species are also rich sources of sulfated polysaccharides with novel structures such as sulfated fucans and galactans (Pomin, 2010).…”
Section: Introductionmentioning
confidence: 99%